2009
DOI: 10.1186/bf03352986
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal and solar cycle variations of electron density gradient scale length, vertical drift and layer height during magnetically quiet days: Implications for Spread F over Trivandrum, India

Abstract: A study has been carried out on the behaviour of electron density gradient scale length, L, vertical drift and layer height, around post sunset hours, during the magnetically quiet days of summer, winter and equinox seasons of solar maximum (2002) and minimum years (1995), using ionosonde data of Trivandrum (8.5• N, 76.5• N) in the Indian longitude sector. The results indicate a clear seasonal and solar cycle variation in all the three parameters. Further, the seasonal variation of equatorial Spread F (ESF) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(22 reference statements)
1
5
1
Order By: Relevance
“…The smallest values exist in March for both solar minimum (1.2 × 10 −2 km −1 ) and maximum (3.7 × 10 −3 km −1 ). These values of L max −1 (0.37–2.1 × 10 −2 km −1 ) are close to that in Mendillo et al [1992] (∼4 × 10 −2 km −1 ), but smaller than that in Ossakow et al [1979] (0.1–0.2 km −1 ) and Manju et al [2009] (0.4–1 × 10 −1 km −1 ). Furthermore, it can be found that there is not clear trend in the monthly L max −1 variations for both two solar epochs.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The smallest values exist in March for both solar minimum (1.2 × 10 −2 km −1 ) and maximum (3.7 × 10 −3 km −1 ). These values of L max −1 (0.37–2.1 × 10 −2 km −1 ) are close to that in Mendillo et al [1992] (∼4 × 10 −2 km −1 ), but smaller than that in Ossakow et al [1979] (0.1–0.2 km −1 ) and Manju et al [2009] (0.4–1 × 10 −1 km −1 ). Furthermore, it can be found that there is not clear trend in the monthly L max −1 variations for both two solar epochs.…”
Section: Resultssupporting
confidence: 61%
“…It is noted that the values of L max −1 during solar minimum are greater than those during solar maximum. Manju et al [2009] also presented that the L −1 values are greater during solar minimum in the Indian sector. This might be because the density gradient is smaller [ Jayachandran et al , 1993] and the ambient density is greater when the F‐layer is located at higher altitude during solar maximum.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…(2008). The magnitude of peak vertical drift is known to control the seasonal and day-to-day variations in the occurrence of equatorial spread F (Manju et al, 2009;Tulasi Ram et al, 2006). where the magnetic field lines aligned with a geographic meridian (Burke et al, 2004;Tsunoda, 2005Tsunoda, , 2010.…”
Section: Spatial Gradient Of T Ec(t)mentioning
confidence: 99%
“…The mechanism of generation of the enhancement in vertical drift just after sunset was detailed by Farley et al (1986). The magnitude of peak vertical drift is known to control the seasonal and dayto-day variations in the occurrence of equatorial spread F (Manju et al, 2009;Tulasi Ram et al, 2006). Figure 8 depicts the quiet-monthly mean of ROTI ave (over ASAB and DEBK: red and black curves) and σ ( TEC/ long) (blue curve) in the year 2014.…”
Section: Relation Between the Equatorial Electric Fieldmentioning
confidence: 99%